Analisis Fundamental Makro, Struktur Kepemilikan Terhadap Kinerja Keuangan dengan Struktur Modal dan Karakteristik Perusahaan sebagai Variabel Intervening pada Perusahaan Plastik & Kemasan yang Terdaftar di Bursa Efek Indonesia - Fadila, Baity Nur; Hwihanus (LANCAH: Jurnal Inovasi dan Tren, 2024)
The purpose of this study is to examine and analyze the relationship between macro fundamental variability, ownership structure to financial performance with capital structure and company characteristics as an intervention in the plastics & packaging sub-sector listed on the Indonesia Stock Exchange. The study population was in 14 companies in the plastic & packaging sub-sector listed on the Indonesia Stock Exchange. The data was analyzed using SmarPLS4 software. The test results show that all hypotheses are rejected which shows that there is no significant influence on the 5% level with a t-table of 1.960 and accepts the first ownership structure against the capital structure with a t-statistic of 2.045. Second, the ownership structure against the characteristics of the company with a t-statistic of 7,849. Third, the ownership structure on financial performance with t-statistics of 3,694. The fourth characteristic of the company on financial performance with t-statistics of 4,612.